Performance of natural chlorophyll Amaranthus and Carica Papaya dye on TiO2 coating in the making of dye sensitized solar cell (DSSC) through the spin coating method - Fernince Ina Pote; Agus Supriyanto; Fahru Nurosyid; Deni Kurniawan (Universitas Sebelas Maret, 2019)
The natural dye extracted from Amaranthus dye and Carica Papaya dye which has been prepared in ethanol solution as a sensitizer on DSSC. The Spin coating method is used so that the deposition on TiO2 gets a homogeneous thin layer on the active area of the FTO substrate. The dye solution was tested for characterization using the Elkahfi I-V Meter and UV-Vis 1601 while the FTO structure substrate that had been prepared as a sandwich was tested using Keithley I-V type 2602A. The result of absorbance of dye is at a wavelength of 400 nm - 800 nm and there is also a shift in wavelength and peak absorption of the dye. The greatest efficiency was obtained from chlorophyll amaranthus which is 0.730% while chlorophyll Carica papaya obtained an efficiency of 0.432%. In the combination of Amaranthus dye and Carica papaya dye, the efficiency was 0.526%. High efficiency on TiO2 electrodes shows good performance on Dye-sensitized solar cells.